Resistencia en teoría: the end of dellusion? - Martín Gutiérrez, Félix (Estudios Ingleses de la Universidad Complutense, 2011)
This review essay tries to explore some impressions and suggestions provoked by Resistencia en teoría, an academic study which places Paul de Man´s controversial essay as a starting point. Based on Dr. Damaso López introductory chapter—delightfully funny, provoking and openly sceptic of the relevance of de Man`s concept of resistence,–this essay brings to our attention some of the linguistic and rhetorical assumptions held by deconstruction in America, the practice of critical reading developed by Paul de Man and the expansion of deconstruction to other areas of critical thinking, especially to the revision of American literary history. At the same time, and connected with this aim the article reviews those essays published by young researchers which tackle significant issues of theoretical debates— gender, sexuality, ecocriticsm, painting and visual art— underlying the critical relevance of “resistance”.